2016
DOI: 10.3390/toxins8110306
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Deoxynivalenol in the Urine of Pregnant Women in the UK

Abstract: Deoxynivalenol (DON) is one of the most commonly occurring trichothecenes, produced mainly by Fusarium graminearum. Little is known about the effect of DON exposure or the levels of DON exposure that occur during pregnancy. The project aimed to provide data on levels of total DON and de-epoxi Deoxynivalenol (DOM-1) in pregnant human urine samples analysed by liquid chromatography-mass spectrometry (LC-MS). Morning urine samples were collected over two consecutive days from 42 volunteers and associated food con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In comparison to pregnant females from Hull, UK [ 21 ] who did not consume any organic foods, three vegetarian individuals in this cohort were regularly consuming organic muesli and multigrain bread. Two of the adults consumed organic products, namely wheat bran rolled flakes daily and organic pasta once a week.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to pregnant females from Hull, UK [ 21 ] who did not consume any organic foods, three vegetarian individuals in this cohort were regularly consuming organic muesli and multigrain bread. Two of the adults consumed organic products, namely wheat bran rolled flakes daily and organic pasta once a week.…”
Section: Discussionmentioning
confidence: 99%
“…Each meal section included examples of food items which belonged to seven food categories, all known to contribute to the consumption of DON. These food categories were in accordance with the validated FFQ used to assess the main dietary sources of DON [ 18 , 19 , 20 ] and included breakfast cereals and snacks, bread, products alternative to bread, pasta, biscuits and bakery products, cereals and similar, and beer. For consistency and ease of recording, the example food items within each category were tabulated with tick boxes as to whether the portion consumed was small, medium, or large.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies which assessed urinary DON levels and its metabolites in adult populations showed exposure levels close to, or even higher than, the PMTDI [ 12 , 15 , 18 ]. There is also interest in investigating DON exposure in potentially susceptible population groups due to their physiological status (e.g., pregnancy) [ 19 ]; dietary habits (e.g., vegetarians) [ 18 ]; and age (i.e., children and adolescents) [ 20 , 21 , 22 ]. Children are considered to be at risk for greater relative DON exposure than adults due to their higher food and fluid intake per kg of body weight compared to adults, child/adult metabolic differences, limited ability for detoxification, and on-going bodily system development including the immune and central nervous system [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, we showed that DON was strongly cytotoxic to MA-10 cells after 48 h of exposure with concentrations as low as 29.63 ng/ml (0.1 µM) and 296.32 ng/ml (1 µM) showing significant cytotoxicity (Eze et al, 2018). Urinary concentrations of 436 ng/ml (1.471 µM) and 1,238 ng/ml (4.178 µM) have been reported for DON and its conjugates in pregnant women (Sarkanj et al, 2013;Wells et al, 2016) and therefore, the concentrations causing cytotoxic effects on MA-10 cells have clinical relevance.…”
Section: Reproductive and Developmental Health Effects Of Deoxynivalementioning
confidence: 97%